Implementasi Jaringan Sensor Nirkabel Dengan Metode Pengiriman Pembagian Slot Waktu Pada Sistem Deteksi Parkir Sepeda Motor - Zonnete Bryllian Dheo; Sabriansyah Rizqika Akbar; Edita Rosana Widasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The conventional methods of vehicle detection system in parking area, usually use a microcontroller as a control system, sensor as component to collect data and cable as data transmission media. The system use one microcontroller to process data from many sensor nodes simultaneously. This situation can cause a problem called data collusion. When data which transmitted simultaneously, it can be interfering each other and allowing the loss of information transmitted by each sensor node. Furthermore, utilization of the cable as a media communication data is considered less efficient when used in the scope of a large area when compared it with the ease of wireless personal communication media that are practical and easy installation process. Against these problems, this research applied a method of scheduling data transmission using Time Division Multiple Access (TDMA) protocol on each client node to avoid collisions. Also applied equalization method of Time-synch Protocol for Sensor Network (TPSN) to support the scheduling method. Furthermore, in this research purposed a method based on wireless data communications using wireless module nRF24L01. Based on the result of implementation, showed that the client node can transmit data according to the schedule that has been obtained without colliding. The data transmission has been successfully carried out in accordance with the delivery time slots that have been applied, where the implementation of delivery time slots are divided into five slots. Implementation time equivalency also been successfully implemented with the average time in the process of equalization of less than 50 seconds.